Study of the prescription pattern of antidiabetics in hypertension with diabetes patients in geriatric population at tertiary care centre: a retrospective observational study - Pal, Avinash D.; Baig, Mirza S.; Rao, Shailaja V. (International Journal of Research in Medical Sciences, 2025)
Background: In India, the elderly population is particularly affected with diabetes and hypertension which is prevalent in this population, leading to complex health challenges, necessitating effective treatment strategies. This study aimed to analyze the prescription patterns of antidiabetic drugs in geriatric patients with type 2 diabetes (T2DM) and hypertension at a tertiary care center. Methods: A retrospective, cross-sectional study was conducted at the government medical college, Chhatrapati Sambhaji Nagar, from March 2023 to March 2024. Prescriptions of patients aged 60 years and above, diagnosed with both diabetes and hypertension, were analyzed. Results: A total of 649 prescriptions were reviewed, with 58.71% of patients being male and 41.29% female. The majority (72.73%) were in the 60-70 age group. Metformin was the most prescribed drug (49.10%), followed by sulfonylureas, particularly glimepiride (30.04%). Combination therapy was the most common treatment approach, with 69.65% of patients receiving two-drug regimens, and 12.02% on three-drug regimens. The most frequent combination was metformin + glimepiride (79.42%). A small proportion (0.92%) received more than three drugs. Generic prescriptions dominated (99.22%), and nearly 89.80% drugs were from the WHO-EML 2023. The average number of drugs per prescription was 1.96. Conclusions: The study highlights metformin as the predominant treatment for elderly patients with diabetes and hypertension, with a strong preference for generic medications and combination therapies. These findings underscore the importance of ongoing evaluation of prescribing patterns to optimize treatment strategies for geriatric patients.